PENERAPAN APLIKASI E-KATALOG KERAMIK DAN GRANIT BERBASIS WEB (STUDI KASUS PT. RYAN PUTRA RITELINDO) - Rapli Muhammad Ardiansah; Bambang Wisnu Widagdo (JUPIK : Jurnal Penelitian Ilmu komputer, 2025)
This research discusses the development of a web-based e-catalog application for PT Ryan Putra Ritelindo using the Extreme Programming (XP) method. The research objective is to increase the effectiveness of product information delivery and overcome the limitations of social media platforms in displaying product details comprehensively. The research methodology uses the XP approach with the stages of planning, design, coding, and testing. System testing is done through blackbox testing, whitebox testing, and user satisfaction testing. The test results showed that the user satisfaction level reached 89.9% and the system manager satisfaction level reached 90%. The implementation of e-catalog successfully increases efficiency in delivering product information, facilitates real-time data updates, and provides better access to product details compared to social media platforms.